2023
DOI: 10.1002/adhm.202203106
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Calcium Ion Nanogluttons Alleviate Periodontitis via Controlling mPTPs

Abstract: The mitochondrial permeability transition (mPT) directly affects mitochondrial function in macrophages. Under inflammatory conditions, mitochondrial calcium ion (mitoCa 2+ ) overload triggers the persistent opening of mPT pores (mPTPs), further aggravating Ca 2+ overload and increasing reactive oxygen species (ROS) to form an adverse cycle. However, there are currently no effective drugs targeting mPTPs to confine or unload excess Ca 2+ . It is novelly demonstrated that the initiation of periodontitis and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…These changes were consistent with the alteration in TCA cycle genes and increased glycolytic gene expression [128]. He et al revealed that under inflammatory conditions, mitochondrial calcium overload in macrophages triggered the persistent opening of mitochondrial permeability transition pores, aggravating calcium overload and inducing mitochondrial dysfunction, forming an adverse cycle which contributed to the activation of periodontitis in vivo [129].…”
Section: Discussionmentioning
confidence: 54%
“…These changes were consistent with the alteration in TCA cycle genes and increased glycolytic gene expression [128]. He et al revealed that under inflammatory conditions, mitochondrial calcium overload in macrophages triggered the persistent opening of mitochondrial permeability transition pores, aggravating calcium overload and inducing mitochondrial dysfunction, forming an adverse cycle which contributed to the activation of periodontitis in vivo [129].…”
Section: Discussionmentioning
confidence: 54%
“…S26 † ). 47 Consequently, the significant mitochondrial depolarization by Ca@DNA–MF has been verified.…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, it is necessary to alleviate inflammation, create a homeostatic immune environment for inflammatory osteolytic diseases, and provide essential elements for regenerative tissue repair. [ 81 ] In conclusion, Se‐nHA/PC microspheres can effectively protect periodontal ligament attachments and alveolar bone from inflammatory tissue destruction and have a promising future for the treatment of periodontal tissues.…”
Section: Resultsmentioning
confidence: 99%